Coastal hydrogeology, by Jiao Jimmy and Vincent Post, 2019. Cambridge University Press, Cambridge, UK. 403 pages. Hardback: price £49.99, ISBN: 9781107030596 - Szymkiewicz, Adam (Geologos, 2022)
Coastal hydrogeology, by Jiao Jimmy and Vincent Post, 2019. Cambridge University Press, Cambridge, UK. 403 pages. Hardback: price £49.99, ISBN: 9781107030596